Accounting in the Lean Enterprise - McVay, Gloria; Kennedy, Frances; Fullerton, Rosemary (Productivity Press, 2017)
Despite the obvious need for transparency, a company's Lean results can continue to hide behind the mask of traditional accounting and dilute the benefits of a Lean implementation. When your organization opts to go Lean, you must empower your accountants with Lean tools that serve the Lean mission. Winner of a Shingo Research and Professional Public.